Elastic-plastic fracture mechanics investigation on offshore structures and materials - Mohammad Zaidi Ariffin (Nanyang Technological University, 2018)
Failure of offshore structures and materials, with complex defects such as multiple cracks and crack-in-corrosion (CIC) that are exposed to extreme tension and bending loads accompanied by high internal pressure, could pose serious complications if not assessed accurately. Existing failure-fracture assessment procedures widely used in the industry are not accurate for situations with large plastic deformation as they are load-controlled based mainly on linear elastic fracture mechanics. In addition, there are no handbook solutions and standards on CIC cases. The thesis demonstrates the novel and high potential applications of nonlinear elastic-plastic fracture mechanics methodologies and assessment protocols to assessing 3-D crack-like defects in offshore structures and pipelines under large strain loading. This project is also a pioneering attempt to use full-field measurement technique (using Thermoelastic Stress Analysis (TSA) and Digital Image Correlation (DIC)) for failure analysis of corroded and CIC offshore materials which might allow for in-situ fracture assessment of defects. Currently there is no standard technique to obtain the J-integral. The advantage of our technique is that the precise location of the crack tip is not required. In addition, the failure analysis on pipelines containing multiple coplanar cracks has been carried out comprehensively with a newly accurate strain-based CTOD estimation schemes proposed (with a predicted error limit of ±5%.). For offshore pipelines, there are significant differences for failure assessment of cracks with/without corrosion damage. The new findings and the proposed simplified corrosion numerical defect model can provide a quick decision tool based on based on load and strain demand/capacity (CTOD and critical CTOD), defects number, size and locations.